Qualitative Microbiological Assessment of Ready-to-Eat Fruits Sold in Selected Areas of Kaduna Metropolis - Shitu, S.; Musa, M. O.; Ayis, E. F.; Anyakudo, M. M. C. (UMYU Journal of Microbiology Research)
Study’s Novelty/Excerpt